PELATIHAN PENINGKATAN KOMPETENSI KOMUNIKASI VERBAL BAGI KELOMPOK NELAYAN KASIAK ANGEK PURUS (KNKAP) KELURAHAN PURUS KECAMATAN PADANG BARAT KOTA PADANG - Revi Marta; Ilham Havifi; Rinaldi Eka Putra; Yayuk Lestari; Diego Diego (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
This training activity aims to improve the verbal and nonverbal communication competencies of fishermen of Kasiak Angek Purus Group (KNKAP) to support the branding of Elo Pukek Thematic Village as a culture-based tourist destination. The implementation of activities was carried out systematically through an initial survey, communication theory training, role play simulation, and interactive evaluation. The results of the training showed a significant improvement in participants' communication skills. Fishermen who previously tended to be passive and lack confidence are now more active, confident, and able to deliver persuasive messages in a structured manner, including in explaining the Maelo Pukek tradition. The training was also fully supported by the local government, demonstrating a shared commitment to the development of local tourism potential. The direct impact of this activity is the improvement of fishermen's communication skills, while the indirect impact is the strengthening of the Elo Pukek Thematic Village branding which is starting to be recognized as a culture-based tourist destination. In addition, a more informative and interactive tourism experience is also able to attract more tourists, which in turn contributes to increasing the potential of the local economy. In conclusion, this training activity successfully achieved its main objectives and had a positive impact on the fishing community. For sustainability, regular monitoring and follow-up trainings are needed so that the results achieved can continue to be applied and improved in the future.